Formal methods teaching : third International Workshop and Tutorial, FMTea 2019, held as part of the third World Congress on Formal Methods, FM 2019, Porto, Portugal, October 7, 2019, Proceedings /: third International Workshop and Tutorial, FMTea 2019, held as part of the third World Congress on Formal Methods, FM 2019, Porto, Portugal, October 7, 2019, Proceedings. (2019) - Unknown
No abstract available